Community water monitoring strategy for the Jorco river micro-basin based on the analysis of physicochemical, microbiological and biological indicators of water quality - Calvo-Brenes, Guillermo (2023)
The profound deficiencies that the country faces in water management policies are reflected in the physicochemical, microbiological and biological contamination of national rivers. The objective of this study was to propose a community water monitoring strategy to improve the management of the Jorco River located in the canton of Acosta. The quality of the water in the upper, middle and lower part of the micro-basin was monitored during the rainy season, using two physicochemical quality indices (ICA): the Dutch and the Calvo-TEC; as well as a biological one: the BMWP-CR. The quality indicators of turbidity, alkalinity, ammonia, ammoniacal nitrogen, nitrates, and fecal coliforms exceeded the permissibility limits in some samples; however, dissolved oxygen showed that there are good levels of oxygen for river recovery. Biochemical oxygen demand was low, indicating low organic load, and macroinvertebrates showed a degraded aquatic ecosystem. The Dutch ICA overestimated the quality of the water with respect to the ICA Calvo-TEC. The latter showed more realistic results because it uses more quality indicators, since it is based on environmental conditions and Costa Rican regulations. The ICA BMWP-CR revealed extreme contamination during the month of greatest rainfall. It was concluded that there is a problem of contamination in the river water whose main causes may be due to the lack of forest cover in the riparian zones, the expansion of coffee cultivation, the discharge of domestic wastewater and livestock activities. Therefore, an action plan was proposed to the municipal council and validated with them, to improve water quality with the participation of different actors in the area.